The Authority of Legislative Institution (A Comparative Study between Regional Represntatives Council of RI and US Senate) - Muhammad Nabil Mabdaunni'am (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
DPD RI is institutionally similar to US Senate. Senate is also a form of regional representation on a legislative institution which its members consist of state representatives and elected in the general election. So, the membership of Senate or DPD RI is based on representation similarity without considering the number of people in a country. This research uses a normative juridical approach, an approach which refers to the law and applicable law. Research findings show that DPD RI and US Senate have a special authority whis is regulated in the constitution of each institution. Similarities and differences between the two institutions can be seen from the legislative authority and election of public officials.